The genus Rhaponticum in Kazakhstan: species diversity, distribution and prospects for practical use. Review - Mamyrova S.А.; Ishmuratova, M.Yu. (Fundamental and Experimental Biology, 2023)
The article presents information on the species composition and distribution of plants of the genus Rhaponticum in Kazakhstan based on literary sources and analysis of herbarium materials. The data of more than 300 samples of the herbarium collections were analyzed, including those from the Institute of Botany and Phytointroduction of the Republic of Kazakhstan, the Institute of Botany of the Academy of Sciences of the Republic of Uzbekistan, Moscow State University, IRPH “Phytochemistry”, the Institute of Biology and Soil of the National Academy of Sciences of the Republic of Kyrgyzstan. More than 30 literary sources were analyzed as well. 6 species of the genus Rhapontiсum were identified within the territory of Kazakhstan, which can be classified according to the following ecological and high-altitude groups. The groups include species growing in the subalpine and alpine meadows of Altai such as Rhaponticum carthamoides (Wiild.) Iljin; plain species such as Rh. Serratuloides (Georgi) Bobr., Rh. Nitidum Fisch.; plants growing on rocky and gravelly slopes of the Western Tien Shan such as Rh. Karatavicum Regel et Shcmalh., Rh. aulieatense Iljin, Rh. namanganicum (Iljin) Dittrich. Medicinal species Rh. carthamoides, Rh. serratuloides and Rh. karatavicum were analyzed to research future prospects of their usage. The perspectives of plants having adaptogenic, psychostimulant, tonic, immunostimulating, anabolic, antibacterial, antioxidant, hemorheological, antiviral, cytotoxic, antiprotozoal properties have been noted and discussed to be used in the medicine, food industry, fodder production, landscape design, beekeeping areas.